Resolution of the equatorial spread F problem: Revisited - Huba, J. D. (Frontiers in Astronomy and Space Sciences, 2023)
An overview of recent advances made in understanding the phenomenon of equatorial spread $F$ (ESF) is presented and a discussion of unresolved issues that need to be addressed. The focus is on research that has occurred in the last decade. The topics include satellite observations, theory, and modeling. The suggested areas that require further exploration are a unified theory of turbulence extending from 100s m to 10s cm, the impact of geomagnetic storms on the development of equatorial spread $F$, the need for accurate thermospheric wind measurements and models, and identifying the underlying physics of ESF in the post-midnight sector during solar minimum.